Fundamental of Entrepreneurship (ENT300) : Business opportunity Sampan noodle / Fiefi Fariesha Mohamad … [et al.] - Mohamad, Fiefi Fariesha; Loren, Norhafizah; Kolek, Norshahaziera; Mohamad Annuar, Nur Effa Dayu; Julaihie, Nur Fatin Syamimi; Rozui @ Rozey 2016915397, Nurul Qatrunada (2018)
The business that we are planning is a restaurant which is call as Sampan Noodle. Our business offer product and services at an affordable price so it can be enjoyed by everyone . We will partner with a few companies to receive supply and to collaborate with their company so that we are able to give the best product and services to our customer.